Mice lacking prostaglandin E receptor subtype 4 manifest disrupted lipid metabolism attributable to impaired triglyceride clearance. Issue 12 (13th August 2015) - Cai, Yin; Ying, Fan; Song, Erfei; Wang, Yu; Xu, Aimin; Vanhoutte, Paul M.; Tang, Eva Hoi‐Ching
ABSTRACT: Upon high‐fat feeding, prostaglandin E receptor subtype 4 (EP4)‐knockout mice gain less body weight than their EP4 +/+ littermates. We investigated the cause of the lean phenotype. The mice showed a 68.8% reduction in weight gain with diminished fat mass that was not attributable to reduced food intake, fat malabsorption, or increased energy expenditure. Plasma triglycerides in the mice were elevated by 244.9%. The increase in plasma triglycerides was independent of changes in hepatic very low density lipoprotein (VLDL)‐triglyceride production or intestinal chylomicron‐triglyceride synthesis. However, VLDL–triglyceride clearance was drastically impaired in the EP4‐knockout mice. The absence of EP4 in mice compromised the activation of lipoprotein lipase (LPL), the key enzyme responsible for trafficking of plasma triglycerides into peripheral tissues. Deficiency in EP4 reduced hepatic mRNA expression of the transcriptional factor cAMP response element binding protein H (by 36.8%) and LPL activators, including apolipoprotein (Apo)a5 (by 40.2%) and Apoc2 (by 61.3%). In summary, the lean phenotype of EP4‐deficient mice resulted from reduction in adipose tissue and accretion of other peripheral organs caused by impaired triglyceride clearance. The findings identify a new metabolic dimension in the physiologic role played by endogenous EP4.—Cai, Y., Ying, F., Song, E., Wang, Y., Xu, A., Vanhoutte, P. M., Tang, E. H.‐C. Mice lacking prostaglandin E receptor subtype 4 manifest disrupted lipid metabolism attributable to impaired triglyceride clearance. FASEB J. 29, 4924–4936 (2015). www.fasebj.org